3-D Spinors, Spin-Weighted Functions and their Applications - Torres del Castillo, Gerardo Francisco ((Progress in Mathematical Physics ;)
Contenido: Rotación y rotacionales (spinors); Algebra de rotacionales; Análisis de rotacionales.